FAKTOR YANG MEMPENGARUHI OBESITAS PADA WUS DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU 2019 - Eva Santi Hutasoit (LPPM Universitas Abdurrab, 2020)
ABSTRACT : Obesity is a state of imbalance between incoming energy and energy coming out for a long time. This excess energy will be stored in the form of fat and fat tissue so that it can result in weight gain. Obesity can be prevented by frequent physical activity by exercising regularly, consuming foods that are low in fat and healthy, maintaining weight in a healthy way. The purpose of this study was to determine the relationship of factors that influence obesity in Fertile Age Women in Payung Sekaki Health Center, Pekanbaru City. This type of research is quantitative with correlational analytic research designs with cross sectional techniques. This research was conducted on October 15 - November 15, 2019. The number of samples was 100 people with a purposive sampling technique. Data collection on knowledge, attitudes and exercise using a questionnaire, fiber intake with FFQ Semi Quantitative interviews. Data analysis was performed with univariate and bivariate data analysis with chi-square test. The results obtained by the incidence of obesity in WUS as much as 60%. Analysis of bivariate data with 95% CI level obtained by factors related to obesity is knowledge factor P value = 0.037 OR 0.405 (0.172 - 0.957, Attitude P value = 0,000, Sports 0.012 OR 3.523 (1,280 - 9,690) .Inrelated factors are intake fiber P value = 0.412. Therefore, prevention and response efforts need to be done by increasing public knowledge and awareness about eating patterns, limiting energy intake in accordance with daily energy needs.